Efeito de frações obtidas da fucoidana de Fucus vesiculosus em modelo experimental de artrite induzida por Zymosan - Cardoso, Maria Leila (2007)
The fucoidan from Fucus vesiculosus is known for having diverse biological properties. This study analyzed the therapeutic action of populations of commercial fucoidan (F. vesiculosus) on zymosan-induced arthritis. Three populations of fucoidan were obtained after acetone fractionation; these were denominated F1 (52.3%), F2 (36.7%) and F3 (10.7%). Chemical analyses showed that F1 contained the largest amount of sulfate ion. The electrophoretic profile shows that the commercial or total fucoidan (TF), different from the other fucoidans and from glycosaminoglycan patterns, is quite polydisperse, which indicates that it is composed of a mixture of sulfate polysaccharides. On the other hand, the fucoidans obtained from TF showed only an electrophoretic band with much lower polydispersion than that observed for TF. Fucoidan F2 showed a migration between fucoidans F1 and F3. Owing to the small amount of mass obtained from F3, we used only fucoidans F1 and F2 in the induced arthritis tests. After 1 hour of induction, we administered F1 or F2 (10, 25 and 50 mg/kg i.p.) or diclofenac sodium (10 mg/kg i.p.) or lumiracoxib (5 mg/kg o.a.) or L-NAME (30 mg/kg i.p.). After 6 hours, we performed analyses of cell influx and nitrite levels in addition to histopathological analysis. Fucoidans F1 and F2 were more potent both in decreasing the number of leukocytes and the amount of nitric oxide found in the synovial fluid. This indicates that the anti-inflammatory mechanism of these fucoidans is not only related to selectin block, but also to nitric oxide synthesis inhibition